Cytokines and immune related gene expression alteration in chicken HD11 cell line following very virulent infectious bursal disease virus infection - Rasoli, Mehdi; Keong, Yeap Swee; Tan, Sheau Wei; Ideris, Aini; Bejo, Mohd Hair; Kaiser, Pete; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Studies have showed that infectious bursal disease virus (IBDV) can infect macrophage and stimulate proinflammatory cytokines. To date, only a few cytokines were evaluated from IBDV infected macrophages. Using multiplex GeXP assay, we were able to quantify up to 27 cytokines and immune related gene expressions from vvIBDV infected chickens HD11 macrophage cell line.